Modeling the antecedents of internet banking service adoption (IBSA) in Jordan: A structural equation modelling (SEM) approach - Al-Majali, Malek; Nik Mat, Nik Kamariah (ARRAY Development, 2011)
After ten years from the introduction of the Internet Banking Services (IBS) by Jordanian banks, the adoption of these services is still quite low. Hence, identifying success factors (SF) to improve the level of IBS adoption is crucial. This paper is concerned with an empirical investigation of success factors that could predict successful IBSA in Jordan through applications of Innovation Diffusion Theory (IDT). The research model consists of six exogenous variables: perceived ease of use, perceived usefulness, compatibility, trialability, trust and awareness and one endogenous: IBSA. 700 questionnaires survey among university staff was implemented and 532 data sets were collected.This represents 76% response rate. After rigorous data screening process such as outliers, normality, reliability and validity, 517 data is ready for structural equation modeling (SEM) analysis. Confirmatory Factor Analysis (CFA) was performed to examine the composite reliability, convergent validity and goodness of fit of individual construct and measurement models. The revised structural model demonstrates significant and positive direct relationships between all of six exogenous variables and IBSA.